Interactive 360-degree Videos in Ginga-NCL Using Head-Mounted-Displays as Second Screen Devices - Souza, Gabriel; Silva, Daniel; Delgado, Matheus; Rodrigues, Renato; Mendes, Paulo R. C.; Amorim, Glauco Fiorott; Guedes, Álan L. V.; Santos, Joel A. F. dos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
The recent availability of HMD devices (Head-Mounted Display) spurred advances in Virtual Reality and Augmented Reality. It allowed scenarios of immersion of users in realistic environments, e.g., synthesized 3D environments for games and simulation, and omnidirectional videos, namely 360° videos. These HMD devices are commonly used in conjunction with home computers or in controlled environments (e.g., museums). However, despite these scenarios, current interactive TV systems still focus on using interactive content in two-dimensional layouts. These systems could use HMDs to provide immersive experiences to viewers. This paper, therefore, presents Guaraná, a player for interactive 360° scenes using HMDs as second screen devices. Guaraná controls a 360 scene execution based on external control from a TV set. Thus, it enables its use in conjunction with an intereactive multimedia application.